2019
DOI: 10.1063/1674-0068/cjcp1812287
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ni nanoclusters-modified brookite TiO2 quasi nanocubes and its photocatalytic hydrogen evolution performance

Abstract: The development of low-cost, earth-abundant and highly-efficient cocatalysts is still important to promote the photocatalytic H 2 evolution reaction over semiconductors. Herein, a series of Ni nanoclusters (NCs) modified brookite TiO 2 quasi nanocubes (BTN) (marked as Ni/BTN) are fabricated via a chemical reduction process. It is found that the loading content and oxidation state of Ni NCs can significantly influence the optical absorption, photocatalytic activity, and stability of Ni/BTN composites. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In contrast to the bulk Ni metal, the nano-scaled Ni species are more propitious to the efficient charge transfer and interface chemical reaction, which is attributed to an enlarged surface area and much more active sites. 60 The nickel nanoparticles with a size of ca. 10 nm could be introduced on CdS by a simple synthetic strategy.…”
Section: Metallic Ni Cocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the bulk Ni metal, the nano-scaled Ni species are more propitious to the efficient charge transfer and interface chemical reaction, which is attributed to an enlarged surface area and much more active sites. 60 The nickel nanoparticles with a size of ca. 10 nm could be introduced on CdS by a simple synthetic strategy.…”
Section: Metallic Ni Cocatalystmentioning
confidence: 99%
“…This trait signifies that the Schottky junction also can be constructed between metallic Ni and semiconductor, and the junction is more beneficial for separation and migration of photo‐excited electrons and holes. In contrast to the bulk Ni metal, the nano‐scaled Ni species are more propitious to the efficient charge transfer and interface chemical reaction, which is attributed to an enlarged surface area and much more active sites 60 . The nickel nanoparticles with a size of ca.…”
Section: Progress Of Ni‐based Cocatalysts For Hydrogen Evolutionmentioning
confidence: 99%
“…Brookite TiO 2 photocatalyst has large band gap (3.1-3.4 eV) which responds only for a small fraction of solar spectrum, leading to low photocatalytic efficiency and poor absorption properties to visible light. To improve the performance of brookite TiO 2 photocatalyst, a great deal of work has been done to improve its photocatalytic activity, including synthesis of pure-phase brookite TiO 2 with different particle sizes or morphologies [15,[17][18][19][20], modification with foreign elements (e.g., cations, anions) [21][22][23][24], and combination with different semiconductor oxide materials, etc [25][26][27][28]. Modification with foreign elements has proven to be one of the most effective strategies to improve the photocatalytic activity of brookite TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Modification with foreign elements has proven to be one of the most effective strategies to improve the photocatalytic activity of brookite TiO 2 . Among the dopants, transition metals have been widely studied due to their unique oxidation state and chemical similarity with Ti, which can induce changes to the bandgap and defects in crystal structure of brookite TiO 2 [22][23][24]29]. Zeng et al [23] reported that the pohotocatalytic activity of brookite TiO 2 for H 2 production was improved significantly by introduction of Ni which offered shorter charge transfer distance by quickly capturing the photoexcited electrons of brookite TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The Sn 3d spectrum consists of two peaks at 486.1 eV and 494.6 eV, which are ascribed to Sn 3d 5/2 and Sn 3d 3/2 , indicating that Sn element exists as Sn 4+[35]. The peaks located at 855.7 eV and 861.8 eV correspond to Ni 2p 3/2 and the peaks located at 873.2 eV and 880.1 eV correspond to Ni 2p 1/2 , suggesting that Ni element exists in the form of +2 valence[14,40,41].…”
mentioning
confidence: 96%